2015
DOI: 10.1097/iop.0000000000000508
|View full text |Cite
|
Sign up to set email alerts
|

A Skin Crease Preserving Modification of Open-Sky Mullerectomy for Blepharoptosis Correction

Abstract: Skin Crease Preserving modified open-sky Muller's muscle-conjunctival resection is an effective technique for correcting blepharoptosis, while normalizing the skin crease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 2 publications
1
4
0
Order By: Relevance
“…1 However, several retrospective series on MMCR have included patients with baseline MRD1 ≤0 mm. 2,5,14,15,18,19,28,29 In the present study, a MRD1 prephenyl of 0 mm was associated with a 60% observed rate of MRD1 success and a 63% predicted rate of MRD1 success. In addition, with each 0.5 mm increase in MRD1 prephenyl, there was a commensurate increase in predicted success (Fig.).…”
Section: Discussionsupporting
confidence: 57%
See 4 more Smart Citations
“…1 However, several retrospective series on MMCR have included patients with baseline MRD1 ≤0 mm. 2,5,14,15,18,19,28,29 In the present study, a MRD1 prephenyl of 0 mm was associated with a 60% observed rate of MRD1 success and a 63% predicted rate of MRD1 success. In addition, with each 0.5 mm increase in MRD1 prephenyl, there was a commensurate increase in predicted success (Fig.).…”
Section: Discussionsupporting
confidence: 57%
“…Studies have defined MMCR success using subjective terminology 2,4 or arbitrary cosmetic scales. 13 In addition, when MRD1 is documented, the outcome most often reported is the change in MRD1 from baseline [3][4][5]7,10,[13][14][15][16][17][18][19] -a measure that does not adequately reflect the likelihood of obtaining a clinically acceptable result. Although racial variations exist for upper eyelid height, 2 standard deviations below the mean normal MRD1 is thought to lie between 2.0 and 2.5 mm, 20,23 and lay observers typically recognize upper eyelid asymmetry when the difference in MRD1 exceeds 1 mm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations